Efficiency of extraction of polycyclic aromatic hydrocarbons from the Paleoproterozoic Here’s Your Chance Pb/Zn/Ag ore deposit and implications for a study of Bitumen II - Holman, Alex; Grice, Kliti; Jaraula, Caroline; Schimmelmann, A.; Brocks, J. (Pergamon, 2012)
Demineralisation of a sedimentary rock with HF liberates a fraction of extractable organic matter (OM) that is not accessible with standard extraction techniques, which is known as Bitumen II. This fraction displays lower maturity parameters than the free extractable OM (Bitumen I). Studies of successive conventional extraction have found that the later steps show a decrease in maturity similar to that observed for Bitumen II. We aimed to investigate whether or not Bitumen II is simply the result of residual Bitumen I left over from the initial extraction. A series of successive Soxhlet extraction steps was performed on a highly mineralised sample from the Paleoproterozoic Here’s Your Chance (HYC) Pb–Zn–Ag deposit in the Northern Territory of Australia. The study showed that the extraction efficiency for polycyclic aromatic hydrocarbons (PAHs) decreased with increasing molecular weight. Maturity parameters based on methyl phenanthrenes generally decreased with successive extraction steps. This is because the thermodynamically more stable β isomers were preferentially extracted over the α isomers, so later extraction steps contained a greater proportion of α isomers. Bitumen II was prepared from a previously-studied sample from the same sample pit. It showed a decrease in maturity parameters relative to Bitumen I, but the distribution of PAHs did not match those of the later Bitumen I extraction steps. We conclude that Bitumen II did not result from incomplete extraction of Bitumen I. As Bitumen II is preserved within the kerogen–mineral matrix, it has potential for tracing the migration and maturation history of ancient or thermally altered systems.